Application of PCR for the detection of tubercle bacilli from retropharyngeal and thyroid abscess: case reports - Bhattarai, Narayan Raj; Rai, Keshav; Baral, Ratna; Chhetri, Shyam Thapa; Paudel, Deepak; Karki, Smriti; Khanal, Basudha (Journal of Chitwan Medical College, 2019)
The diagnosis of extra-pulmonary tuberculosis by Mycobacterium tuberculosis infection in retropharyngeal and thyroid abscess is challenging due to a lack of rapid, sensitive and specific diagnostic assay. Hence, we evaluated the performance of highly sensitive polymerase chain reaction (PCR) to detect the M. tuberculosis in the retropharyngeal and thyroid abscess. The microscopy and culture were negative test result however; PCR result had demonstrated the presence of M. tuberculosis in the same specimens with retropharyngeal and thyroid abscess. Therefore, it is recommended to perform PCR to detect undiagnosed cases, which were not detected by conventional approaches for the diagnosis, of extra-pulmonary tuberculosis.